Short-term exercise as a cognitive enhancer : an investigation of the underlying mechanisms - Bechara, Ranya (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Physical exercise is one of the most potent and effective cognitive enhancers we know. Unequivocal evidence in both humans and animals has shown that exercise can induce robust and consistent improvements in performance in different memory tasks. Exercise has also been shown to boost neurogenic and neurotrophic activity in the brain. The mechanisms underlying these effects are still not well understood, and as a result, the therapeutic applicability of exercise has been limited. Although substantial research now points to brain-derived neurotrophic factor (BDNF) as the central mediator of the positive effects of exercise on both cognition and neurogenesis, direct evidence is lacking. Furthermore, it is unclear how exactly exercise causes increases in BDNF, and how these increases translate to improvements in memory. To address these and other gaps in the literature, we used a multidisciplinary approach to investigate the mechanisms of short-term exercise-induced cognitive enhancement in the male Wistar rat, by combining behavioural, cellular, molecular, and imaging techniques.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin